Impact of the COVID-19 pandemic on community-based brain injury associations across Canada: a cross-sectional survey study - Salazar, Ana Paula; Bottari, Carolina; Lecours, Sophie; McDonald, Michelle; Gignac, Monique A. M.; Swaine, Bonnie; Schmidt, Julia; Lemsky, Carolyn; Brosda, Ashley; Engel, Lisa (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic created new difficulties for people living with brain injury, their families, and caregivers while amplifying the challenges of community-based associations that support them. We aimed to understand the effects of the pandemic on clients who live with brain injury, as well as on the provision of community brain injury services/programs in Canada. Methods Online cross-sectional survey conducted in January 2022. Representatives of brain injury associations across Canada completed the 31 open- and closed-ended questions about meeting clients’ needs, addressing public health guidelines, and sustaining the association. Data were analyzed using descriptive statistics (close-ended questions) and qualitative content analysis (open-ended questions). Results Of the 45 key representatives from associations in Pacific/Western (40%), Central (56%), and Atlantic Canada (4%), the majority were paid executive directors (67%). Participants reported that the most frequent psychosocial challenges experienced by their clients during the pandemic were social isolation (98%), loneliness (96%), and anxiety (93%). To alleviate these challenges, associations implemented wellness checks and psychosocial support. Most respondents (91%) affirmed that clients faced multiple technological barriers, such as a lack of technological knowledge and financial resources for devices and/or internet. In the open-ended questions, twenty-nine (64%) associations reported providing clients with devices, technology training, and assistance. Regarding public health measures, thirty (67%) respondents reported that clients had challenges understanding and/or following public health guidelines. Forty-two associations (93%) provided tailored information to help clients understand and comply with public health measures. Although associations (67%) received pandemic-related funding from the Canadian government they still struggled with the association’s sustainability. Thirty-four (76%) lost funding or financial resources that prevented them from delivering programs or required the use of reserve funds to continue to do so. Only 56% reported receiving sufficient funding to address additional COVID-19-related expenses. Conclusion Although the pandemic added further challenges to the sustainability of brain injury associations across Canada, they quickly adapted services/programs to respond to the increasing and varied needs of clients, while complying with protective measures. To ensure community associations’ survival it is essential to aptly recognize the vital role played by these associations within the brain injury care continuum.